Comparative analysis between resinoid and vitrified bond grinding wheel under interrupted cutting - Ribeiro, Fernando Sabino Fonteque [UNESP]; Lopes, Jose Claudio [UNESP]; Talon, Anthony Gaspar [UNESP]; Garcia, Mateus Vinicius [UNESP]; Mello, Hamilton Jose de [UNESP]; Sanchez, Luiz Eduardo De Angelo [UNESP]; Aguiar, Paulo Roberto de [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
The final quality of mechanical components is directly linked to the efficiency of the machining processes to which it is subjected. In this sense, grinding can provide high standards of surface and geometric quality for mechanical components, since these characteristics are increasingly necessary for the automotive and aerospace sectors. However, the complexity of the mechanical components creates increasing difficulties for grinding. Workpieces with geometric interruptions, as in the case of gears, splined shafts, pistons, and crankshafts generate mechanical impacts and aggravate the thermal gradients during grinding, causing errors of shape, drop in surface quality and reduction in the life of the cutting tool. However, few studies on better conditions for interrupted cut grinding are seen, thus making it difficult to determine ideal grinding conditions. Thus, the present experimental investigation aims to make a comparison between cylindrical grinding of workpieces of hardened AISI 4340 steel with two, six, and twelve geometric interruptions, comparing them with the grinding workpieces without interruptions, applying white aluminum oxide wheels with vitrified and resinoid bonds. Results in terms of surface roughness, roundness deviation, acoustic emission, grinding power, diametrical wheel wear, and micrography are pointed out, indicating that the greater rigidity of the vitrified bond can be harmful during the grinding of workpieces with interrupted geometry.
Keywords: Interrupted grinding; Aluminum oxide grinding wheel; Vitrified bond; Resinoid bond; AISI 4340 hardened steel